Quantification of health and environmental risks due to radionuclides in limestone mining regions of Ariyalur, South India. Issue 2 (4th March 2022) - Kumar, E.; Subramani, T.; Li, Peiyue; Karunanidhi, D.
Abstract: In the earth's crust, there is an occurrence of naturally occurring radioactive material (NORM) in all parts of the environment as well as in sediment form based on the formation of rock and soil and its geological setting. The radionuclides become hazardous to human health and the environment due to anthropogenic activities, especially mining. The present work focused on quantifying primordial radionuclides from the collected soil samples in the mining and non-mining regions of Ariyalur taluk, Tamil Nadu, South India. The radiological parameters for the collected samples were assessed, and it was found that the level of activity concentrations of certain samples was of higher value compared to global average value, particularly in mining areas. Spatial distribution and geo-statistical analysis of the collected samples were mapped and interpreted, respectively. Using OLS and GWR tools, regression analysis of health and ecological risk parameters with the primordial radionuclides were correlated. Quantitatively, the present study evaluated the health and ecological risk in mining and non-mining regions of Ariyalur taluk. In addition to this, the calculated value of risk parameters in mining and non-mining regions was compared with the global value regarding the nature of rock and soil.